Thiamine dose response in human milk with supplementation among lactating women in Cambodia: study protocol for a double-blind, four-parallel arm randomised controlled trial - Kyly C Whitfield; Hou Kroeun; Tim Green; Frank T Wieringa; Mam Borath; Prak Sophonneary; Jeffrey R Measelle; Dare Baldwin; Lisa N Yelland; Shalem Leemaqz; Kathleen Chan; Jelisa Gallant (BMJ Open)
Introduction Thiamine (vitamin B1) deficiency remains a concern in Cambodia where women with low thiamine intake produce thiamine-poor milk, putting their breastfed infants at risk of impaired cognitive development and potentially fatal infantile beriberi. Thiamine fortification of salt is a potentially low-cost, passive means of combating thiamine deficiency; however, both the dose of thiamine required to optimise milk thiamine concentrations as well as usual salt intake of lactating women are unknown.Methods and analysis In this community-based randomised controlled trial, 320 lactating women from Kampong Thom, Cambodia will be randomised to one of four groups to consume one capsule daily containing 0, 1.2, 2.4 or 10 mg thiamine as thiamine hydrochloride, between 2 and 24 weeks postnatal. The primary objective is to estimate the dose where additional maternal intake of thiamine no longer meaningfully increases infant thiamine diphosphate concentrations 24 weeks postnatally. At 2, 12 and 24 weeks, we will collect sociodemographic, nutrition and health information, a battery of cognitive assessments, maternal (2 and 24 weeks) and infant (24 weeks only) venous blood samples (biomarkers: ThDP and transketolase activity) and human milk samples (also at 4 weeks; biomarker: milk thiamine concentrations). All participants and their families will consume study-provided salt ad libitum throughout the trial, and we will measure salt disappearance each fortnight. Repeat weighed salt intakes and urinary sodium concentrations will be measured among a subset of 100 participants. Parameters of Emax dose–response curves will be estimated using non-linear least squares models with both ‘intention to treat’ and a secondary ‘per-protocol’ (capsule compliance ≥80%) analyses.Ethics and dissemination Ethical approval was obtained in Cambodia (National Ethics Committee for Health Research 112/250NECHR), Canada (Mount Saint Vincent University Research Ethics Board 2017–141) and the USA (University of Oregon Institutional Review Board 07052018.008). Results will be shared with participants’ communities, as well as relevant government and scientific stakeholders via presentations, academic manuscripts and consultations.Trial registration number NCT03616288.